Employee Turnover Intention of SMEs: A Case Study in China - Yao, Yixuan; Zeng, Hongjun (International Journal of Small and Medium Enterprises, 2019)
Through the empirical analysis and test of 2106 valid questionnaires of employees of small and medium enterprises(SMEs) in China, the article presents the influence mechanism of the sense of fairness of salary distribution on employees' turnover intention based on the cross angle of internal and external factors. The theory of organizational commitment and perception of external job opportunities was introduced and applied AMOS 22.0 to conduct confirmatory factor analysis on the scale. Then applies SPSS 23.0 to establish a hierarchical linear regression model to analyze the impact of the fairness of salary distribution on turnover intention and analyze organizational commitment and the mediating and regulating role of external job opportunities. The results indicate that the sense of fairness in salary distribution and organizational commitment can effectively reduce employees' turnover intention, and employees' perceived external job opportunities moderate this inhibition.